Sewage sludge as an alternative resource: Optimization of media for citric acid production - Alam, Md. Zahangir; Mohamad Hanapi, Nur Hanis; Abdulkarim, Mohd Ismail (2009)
Sewage is the largest contributor of organic pollution to water resources as well as to surrounding environments all over the world. In Malaysia, its contribution is top listed (64.4%), followed by animal husbandry wastes (32.6%), agro-based (1.7%) and industrial effluent (1.3%) in terms of the BOD load (Alam et al. 2009). Approximately 4.2 million cubic meters of sewage sludge (pure organic waste without mixing with the industrial waste) is produced annually by Indah Water Konsortium (IWK), a national sewerage company in Malaysia and the total cost of managing is estimated at RM 1 billion (Kadir and Velayutham, 1999). The country has to adopt a practical, economic, and acceptable approach in managing and disposing sewage sludge. Present practice is either to co-dispose it with solid waste at landfill sites or direct disposal in shallow trenches (Zain et al., 2001). However, the safe and environmental-friendly disposal of this huge quantity of sludge is the main concern of IWK. Sludge can be a very good source of carbon, nitrogen, phosphorus and other nutrients for many microbial processes. Therefore, the production of citric acid using sewage sludge as the sole media would be an alternative to overcome sludge disposal problem as well as to fulfill the demand of this organic acid globally